1973
DOI: 10.1007/bf02633564
|View full text |Cite
|
Sign up to set email alerts
|

Sterol composition of 19 vegetable oils

Abstract: The unsaponifiables from 19 vegetable oils were divided into a sterol and three other fractions by thin‐layer chromatography. All except olive and palm kernel oils gave the sterol fraction in a large quantity. Compositions of the sterol fractions were determined by gas liquid chromatography. Identification of each sterol was carried out by gas liquid chromatography and combined gas chromatograph‐mass spectrometry. Campesterol, stigmasterol and β‐sitosterol were present in all oils, and a minor amount of choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
85
0
8

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(102 citation statements)
references
References 16 publications
9
85
0
8
Order By: Relevance
“…The high cholesterol content in tomato seed oil gives rise to problems in analytical interpretation when controlling the purity of vegetable as well as animal fats. Moreover, the results of the present study confirmed the wide distribution of 24-methylenecholesterol in vegetable oils, which initially was believed to be widely distributed in marine organisms (37,38). The sterol fraction from tomato seed oil consists mainly of A^-sterols with small proportions of A^-sterols as in most vegetable oils (38).…”
Section: Resultssupporting
confidence: 82%
“…The high cholesterol content in tomato seed oil gives rise to problems in analytical interpretation when controlling the purity of vegetable as well as animal fats. Moreover, the results of the present study confirmed the wide distribution of 24-methylenecholesterol in vegetable oils, which initially was believed to be widely distributed in marine organisms (37,38). The sterol fraction from tomato seed oil consists mainly of A^-sterols with small proportions of A^-sterols as in most vegetable oils (38).…”
Section: Resultssupporting
confidence: 82%
“…The sterol content in the sunflower, soybean or rapeseed oils added is shown in Table 2. It corresponds well with the data by ITOH et al (1973). The percentage shares of respective sterols in model samples are shown in Table 3.…”
Section: Resultssupporting
confidence: 88%
“…However, this fraction contains a wide spectrum of other compounds in addition to sterols, such as higher hydrocarbons, aliphatic alcohols, tocoferols, triterpenebased alcohols, and waxes (EISNER et al 1963(EISNER et al , 1965(EISNER et al , 1966 These compounds may interfere with the following analysis of the sterol fraction using capillary GC and a variety of methods is used for their removal. One of the most frequently used is fractionation using a preparative thin layer chromatography (TLC) (AMATI 1971;ITOH 1973;FREGA 1992;JIMENÉZ & GONZÁLEZ 1996). This method, however, although frequently criticized for its time con-sumption and laborious work, continues to be the official method adopted in the above-mentioned Regulation of the Commission Regulation No.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the sterols detected by GLC are confirmed by GC -MS to be campsterol, stigmasterol, B-sitosterol and 7-stigmasterol as shown from the m/ e fragments (table III). The fragments from 7-stigmasterol of halophyte, major sterol, found to be similar to those reported by Itoh et al (16). The presence of 7- stigmasterol as major constituent of halophyte sterols is peculiar and is unlike other plants which has Bsltosterol as a major component.…”
Section: Resultssupporting
confidence: 87%